Synaptic vesicles position complexin to block spontaneous fusion - Wragg, Rachel T. (2013)
Synapses continually replenish their synaptic vesicle (SV) pools while suppressing spontaneous fusion events, thus maintaining a high dynamic range in response to physiological stimuli. The presynaptic protein complexin can both promote and inhibit fusion through interactions between its alpha-helical domain and the SNARE complex. In addition, complexin’s C-terminal half is required for the inhibition of spontaneous fusion in worm, fly, and mouse, although the molecular mechanism remains unexplained. We show here that complexin’s C-terminal domain binds lipids through a novel protein motif, permitting complexin to inhibit spontaneous exocytosis in vivo by targeting complexin to SVs. We propose that the SV pool serves as a platform to sequester and position complexin where it can intercept the rapidly assembling SNAREs and control the rate of spontaneous fusion.